Programming in Vagus nerve stimulation therapy: Consensus from a Nordic Delphi Panel - Henning, Oliver; Andersen, Noemi Becser; Asztely, Fredrik; Ben-Menachem, Elinor; Gauffin, Helena; Gerstner, Thorsten; Gordon, Lisa; Hikmat, Omar; Ingebrigtsen, Susanne; Kolbjer, Sintia; Kostov, Hrisimir; Lamusuo, Salla; et al. (Elsevier BV, 2026)
Purpose
Despite VNS therapy being established broadly as a second line treatment for drug resistant epilepsy, there are currently no guidelines or recommendations giving sufficient and detailed guidance and suggestions to fully utilize the increasing array of parameter options.
Methods
A panel of 22 experts from the Nordic countries (6 were pediatric neurologists, 14 neurologists and 2 treating both pediatric and adult patients) was assembled to share their experience with VNS therapy using a 5-step Delphi approach. Agreement level ≥80% was considered strong consensus and 60 to79% was considered medium consensus.
Results
After the third round of the Delphi process there were 70 statements in different sections as: How to start the VNS after implantation (9 statements), How to do further adjustment after the initial phase (13 statements), How to use Autostimulation mode (14 statements), How to use scheduled programming (8 statements), Are there special settings for special seizure types/diagnosis (6 statements), How to use day-night programming (3 statements), What to know about Magnet mode (6 statements), How to manage side effects (3 statements), Considerations about gender/age and patient preferences (4 statements), and Practical programming (4 statements). In 46 statements (65.7%) the panel reached a strong consensus, in 11 (17.7%) a medium consensus, and in 13 (18.6%) no consensus was achieved.
Conclusion
The recommendations of the Delphi panel emphasize proactive deployment of available stimulation options including build up in duty cycle and the use of rapid cycling as well as increasing the output current if response with primary target current is insufficient. Additionally, the usage of Magnet mode and Autostimulation mode were encouraged. Guidance on how to use the newest stimulation options such as day-and-night and scheduled programming for improved feasibility and tolerability is provided.